R/V NATSUSHIMA NT07-19 Cruise Data - JAMSTEC (JAMSTEC, 2007)
[CRUISE DATA] This site includes a cruise dataset acquired in NT07-19 on R/V NATSUSHIMA from 2007-09-15 to 2007-09-18.
Observation contents: Bathymetry, Expendable Bathythermograph
Keywords: Research cruise; R/V NATSUSHIMA; oceans